Mechanisms of change in self-concept and well-being following songwriting interventions for people in the early phase of neurorehabilitation. Issue 1 (1st June 2016) - Baker, Felicity; Rickard, Nikki; Tamplin, Jeanette; Roddy, Chantal
Abstract : Background : This study aimed to construct knowledge about the mechanisms of change active during a songwriting intervention for people in early stage recovery post acquired neurological injury. Methods : A total of 10 participants engaged in a 12-session songwriting programme that targeted examination of self-concept. Measures of self-concept, depression, anxiety, affect, satisfaction with life and flourishing were collected pre-, mid- and post-intervention, and compared with repeated measures of flow and meaningfulness of songwriting. Discussion : Medium effects were found for changes in self-concept ( d = 0.557) and depression ( d = 0.682). Improvements in self-concept over time were associated with decreases in depression, anxiety and negative affect, and an increase in flourishing and positive affect. Strong experiences of flow were not positively correlated with positive changes to self-concept and well-being, whereas deriving high levels of meaning were associated with increased negative affect, increased anxiety and reduced emotional suppression. Conclusions : Songwriting interventions appear positively associated with enhanced well-being. Findings suggest that people who find songwriting has strong meaning for them might be more likely to start accepting their emotions and as a result experience increases in anxiety and depression.